Assessment of noise annoyance level of shield tunneling machine drivers under noisy environments based on combined physiological activities. (August 2021) - Xing, Xuejiao; Li, Heng; Zhong, Botao; Qiu, Luting; Luo, Hanbin; Yu, Qunzhou; Hou, Jun; Li, Lang
Highlights: Influence factors to noise annoyance at the individual level were summarized. The shield tunneling machine driver was focused, and an assessment model was proposed to index a driver's noise annoyance level and the ability to adapt to noisy working environment. Measures (e.g., pre-service screening to filter out unqualified individuals) can be proposed to support better noise management and mental status management of workers. The research results can be extended to other working fields exposing to noisy environment. Abstract: Noise annoyance is widely recognized as an expression of psychological strain in acoustic environments. It is closely related to the cognitive capability, risk perception, and decision-making ability of workers and can lead to unsafe behavior and unsatisfactory work performance. Considering the unique working properties and environment, a shield tunneling machine driver should maintain a healthy mental status without severe annoyance effects. In this study, considering the comprehensive responses to noisy environments and individual differences in noise perception, the factors affecting noise annoyance at the individual level were analyzed. An assessment model based on the combined effects of physiological activities in electrocardiography and electroencephalography was proposed to index a driver's noise annoyance level and ability to adapt to a noisy working environment. Through preservice screening based on the assessment model, individuals with an unqualified mental status for shield tunneling machine operation can be excluded to avoid potential operational risks. Additionally, corresponding initiatives (e.g., sound conditioning training) can be implemented in the pre-post specialty training to improve the worker's adaptability to a noisy working environment.